Phytochemical Profiling, Chromatographic Analysis, and In Silico Evaluation of Phyllanthus fraternus Webster as a Dual Inhibitor of TNF-α and IL-6 in Rheumatoid Arthritis (International Journal of Food and Nutritional Sciences, 2022)
Phyllanthus fraternus Webster, a member of the Euphorbiaceae family, has been widely recognized in traditional medicine for its hepatoprotective and anti-inflammatory properties, yet its molecular mechanisms underlying anti-arthritic activity remain unexplored. This study aimed to investigate the phytochemical composition and in silico anti-inflammatory potential of P. fraternus against key pro-inflammatory cytokines, tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6), which are central to the pathogenesis of rheumatoid arthritis. The plant extract was prepared by Soxhlet extraction with 80% ethanol and fractionated successively using solvents of increasing polarity. Phytochemical screening, high-performance thin-layer chromatography (HPTLC), and Fourier transform infrared spectroscopy (FT-IR) confirmed the presence of lignans and polyphenols, including phyllanthin, hypophyllanthin, gallic acid, ellagic acid, and corilagin. Molecular docking simulations using AutoDock Vina revealed that phyllanthin exhibited the strongest binding affinity toward TNF-α (-9.7 kcal/mol) and IL-6 (-9.1 kcal/mol), outperforming the standard drug methotrexate (-6.8 and -6.4 kcal/mol, respectively). The 2D and 3D interaction analyses demonstrated stable hydrogen bonding with residues GLY121 and TYR151 and π-π interactions with TYR119 and LEU55 in the TNF-α binding pocket. The results suggest that the high lignan content of P. fraternus, particularly phyllanthin, contributes to its potent dual inhibition of TNF-α and IL-6. These findings provide a molecular rationale for the traditional use of P. fraternus in treating inflammatory and arthritic conditions and highlight its potential as a promising source for natural anti-inflammatory agents.